Mineral Trioxide Aggregate-based Endodontic Sealer Stimulates Hydroxyapatite Nucleation in Human Osteoblast-like Cell Culture - Salles, Loise Pedrosa [UNESP]; Gomes-Cornelio, Ana Livia [UNESP]; Guimaraes, Felipe Coutinho; Herrera, Bruno Schneider [UNESP]; Bao, Sonia Nair; Rossa-Junior, Carlos [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Tanomaru-Filho, Mario [UNESP] (Elsevier B.V., 2012)
Introduction: The main purpose of this study was to evaluate the biocompatibility and bioactivity of a new mineral trioxide aggregate (MTA)-based endodontic sealer, MTA Fillapex (MTA-F; Angelus, Londrina, Brazil), in human cell culture. Methods: Human osteoblast-like cells (Saos-2) were exposed for 1, 2, 3, and 7 days to MTA-F, Epiphany SE (EP-SE; SybronEndo, Orange, CA), and zinc oxide-eugenol sealer (ZOE). Unexposed cultures were the control group (CT). The viability of the cells was assessed by MTT assay and the morphology by scanning electron microscopy (SEM). The bioactivity of MTA-F was evaluated by alkaline phosphatase activity (ALP) and the detection of calcium deposits in the culture with alizarin red stain (ARS). Energy-dispersive X-ray spectroscopy (EDS) was used to chemically characterize the hydroxyapatite crystallites (HAP). Saos-2 cells were cultured for 21 days for ARS and SEM/EDS. ARS results were expressed as the number of stained nodules per area. Statistical analysis was performed with analysis of variance and Bonferroni tests (P < .01). Results: MTA-F exposure for 1, 2, and 3 days resulted in increased cytotoxicity. In contrast, viability increased after 7 days of exposure to MTA-F. Exposure to EP-SE and ZOE was cytotoxic at all time points. At day 7, ALP activity increase was significant in the MTA-F group. MTA-F presented the highest percentage of ARS-stained nodules (MTA-F > CT > EP-SE > ZOE). SEM/EDS analysis showed hydroxyapatite crystals only in the MTA-F and CT groups. In the MTA-F group, crystallite morphology and chemical composition were different from CT. Conclusions: After setting, the cytotoxicity of MTA-F decreases and the sealer present; suitable bioactivity to stimulate HAP crystal nucleation. (J Endod 2012;38:971-976)
Keywords: Bioactivity; biocompatibility; hydroxyapatite; mineral trioxide aggregate sealer